Factors Influencing the Choice of Health Care Provider during Childbirth by Women in Ibadan, Oyo State, Nigeria (2017)
Background: Exclusive breastfeeding (EBF) is known to have wide range of health benefits for mothers and children alike. The sustenance of lactation is found to be problematic for some women resulting in low achievement of EBF. Objective: To determine the perceived factors that influence lactation and breastfeeding duration amongst women in Ibadan. Methods: This study was a cross-sectional survey. Consecutive sampling method was used to select 160 respondents from selected infant welfare clinics. Data was collected using self- administered questionnaires after due approvals. Data was analysed using both descriptive and inferential statistics. (50.6% and 49.4% Results: Most (78.1%) of the respondents believe that breast milk is sufficient for the first six months of life and majority of the respondents (98.1%) intended to breastfeed. Perception on lactation and breastfeeding were on the average respectively). There was no significant association between decision to breastfeed and exclusive breastfeeding (p= 0.514). association between fluid intake and lactation (p=0.410). Exclusive breastfeeding was mainly influenced by perceived breast milk insufficiency (OR=0.174, CI=0.071-0.429, P=0.001). No Conclusion: Most women are interested in breastfeeding exclusively for six months but some are unable to, because of their perceived breast milk insufficiency. More information on process of lactation should be provided in Antenatal clinics.